Maintaining a sense of normality with the help of others: Lived experiences of facilitators and barriers to Lupus adjustment - Silva-Ribeiro, S.; Bernardes, S. F.; Marques, M. M.; Godinho, C. A. (Journal of Health Psychology, 2025)
Systemic lupus erythematosus (SLE) has a high detrimental impact on individuals’ quality of life. Identifying key factors associated with SLE adjustment is crucial for intervention development, yet there is no previous research exploring the perspectives of individuals with SLE regarding illness adjustment’ facilitating or hindering factors. In this qualitative study, 16 individual semi-structured interviews with Portuguese adults with SLE (13 women) were conducted to explore perceived facilitators and barriers to illness adjustment. A reflexive thematic analysis revealed that efforts toward maintaining a normal life, optimism, keeping engaged in meaningful activities, accessing reliable illness-related information, and having supportive relationships were core facilitators of SLE adjustment. Main barriers included inability to maintain normality, engaging in excessive activity, pessimism, being unsupported or stigmatized, and not having access to reliable illness-related information. These findings unveil potential targets for psychosocial and behavioral interventions aimed at enhancing the quality of life for individuals with SLE.